2021
DOI: 10.3390/ijerph181910289
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review on Minimum Foot Clearance: An Exploration of Level-Ground Clearance in Individuals with Abnormal Gait

Abstract: Background: Falls are a major health concern, with one in three adults over the age of 65 falling each year. A key gait parameter that is indicative of tripping is minimum foot clearance (MFC), which occurs during the mid-swing phase of gait. This is the second of a two-part scoping review on MFC literature. The aim of this paper is to identify vulnerable populations and conditions that impact MFC mean or median relative to controls. This information will inform future design/maintenance standards and outdoor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This difference in the number of analyzed strides might explain the difference in the quality of estimation, as analyzing a lower number of strides might lead to less data variability and to consequently more accurate estimations. The estimation of the paretic minimum foot clearance [ r = 0.89; MAE = 0.01 m; ICC(A,1) = 0.812; ICC(C,1) = 0.848] was found to be robust enough to be used in a clinical environment ( Al Bochi et al, 2021) . However, we have not found any other study that validated the estimation of this metric using IMUs in participants after stroke ( Yang et al, 2013 ; Parisi et al, 2016 ; Visi et al, 2017 ; Wang et al, 2018 ; Feuvrier et al, 2020 ; Arens et al, 2021 ; Arumukhom Revi et al, 2021 ; Laidig et al, 2021 ; Hendriks et al, 2022 ) or with other brain injuries ( Bourgeois et al, 2014 ; Sijobert et al, 2015 ; Moon et al, 2017 ; Behboodi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This difference in the number of analyzed strides might explain the difference in the quality of estimation, as analyzing a lower number of strides might lead to less data variability and to consequently more accurate estimations. The estimation of the paretic minimum foot clearance [ r = 0.89; MAE = 0.01 m; ICC(A,1) = 0.812; ICC(C,1) = 0.848] was found to be robust enough to be used in a clinical environment ( Al Bochi et al, 2021) . However, we have not found any other study that validated the estimation of this metric using IMUs in participants after stroke ( Yang et al, 2013 ; Parisi et al, 2016 ; Visi et al, 2017 ; Wang et al, 2018 ; Feuvrier et al, 2020 ; Arens et al, 2021 ; Arumukhom Revi et al, 2021 ; Laidig et al, 2021 ; Hendriks et al, 2022 ) or with other brain injuries ( Bourgeois et al, 2014 ; Sijobert et al, 2015 ; Moon et al, 2017 ; Behboodi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on the measurement modality of MFC are discussed further in this paper. Studies focusing on MFC values and how it is affected by various conditions are discussed in our companion paper [16].…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…We also review the suitability of using these modalities and methods for the estimation of MFC values on outdoor walkways by comparing the performance, portability, and complexity of each system. A companion paper answers RQ2 and identifies conditions that impact MFC and the range of MFC values individuals with these conditions exhibit [16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the importance of foot activity has been recognized [ 14 , 15 ]. During a normal walk, the heel initially makes ground contact.…”
Section: Introductionmentioning
confidence: 99%
“…Pereira and Gonçalves investigated the effect of fatigue on motion patterns by walking on a treadmill for 20 min and showed that this fatigue was not high enough to change the motion patterns in older adults [ 25 ]. The effect of fatigue on MTC has not been well-investigated [ 14 ]. A technique to imitate the fatigue effect in older adults has recently been developed [ 26 ].…”
Section: Introductionmentioning
confidence: 99%